Rational Design of Superior, Coking‐Resistant, Nickel‐Based Anodes through Tailoring Interfacial Reactions for Solid Oxide Fuel Cells Operated on Methane Fuel. Issue 18 (15th August 2018) - Qu, Jifa; Wang, Wei; Chen, Yubo; Li, Haidong; Zhong, Yijun; Yang, Guangming; Zhou, Wei; Shao, Zongping
Abstract: The reaction between a Ni−Y2 O3 ‐stabilized ZrO2 (Ni‐YSZ) cermet anode and La5.4 WO12− δ (LW) during cell fabrication is utilized to reduce carbon deposition in solid oxide fuel cells operated on methane fuel. The effect of the phase reactions on the microstructure, electrical conductivity, chemical interactions, and coking resistance of the anodes are systematically investigated. Ni x W y and La‐doped YSZ are formed by phase reactions and the synergistic effect between them increases the coking resistance dramatically. 2 wt % is demonstrated to be the optimal amount of LW to modify Ni‐YSZ to achieve best coking resistance. The cell with Ni‐YSZ‐2 wt % LW anode demonstrates a superior peak power density of 943 mW cm −2 at 800 °C with humidified methane as fuel, which is 10 % higher than that of Ni‐YSZ (859 mW cm −2 ). Furthermore, the cell is stable for 200 h in methane fuel with no clear performance degradation while the cell with unmodified anode fails after 0.5 h's operation. In summary, we provide a new way to rationally design Ni‐based cermet anode with high electrocatalytic activity and excellent coking resistance. Abstract : Coating prevention : A moderate amount of La5.4 WO12− δ (LW) leads to a beneficial phase reaction in a Ni−Y2 O3 ‐stabilized ZrO2 (Ni‐YSZ) anode and the products shows a synergistic effect that increases the coking resistance of the anode dramatically. Excellent coking resistance is mainly assigned to adsorbed water as a result of WO3− x − δ, which greatly promotes the removal of deposited carbon as CO2 .